Assessing translocation management techniques through experimental trials: a case study of the endangered shrub Persoonia hirsuta. Issue 7 (23rd November 2021) - Andres, Samantha E.; Powell, Jeff R.; Gregory, David; Offord, Catherine A.; Emery, Nathan J.
Abstract : Translocation is commonly used in the conservation of threatened species to help mitigate the risk of local extinctions. However, translocations are often limited by knowledge of the species ecological requirements that promote persistence in the landscape. Small translocation trials with a strong experimental design can help to address species knowledge gaps and identify effective strategies for the successful establishment of a threatened species prior to implementing full‐scale planting regimes. In this study, we experimentally translocated 128 plants of the endangered Persoonia hirsuta (Proteaceae) at a dry sclerophyll mining offset in New South Wales (NSW), Australia, and investigated the effects of propagation type (seeds and vegetative cuttings), plant guards, and mulching on short‐term plant growth and survival. Transplants were impacted by herbivory and unprecedented extreme temperatures over summer 2019–2020 with 25 of the 128 plants surviving after 20 months of monitoring. Among the surviving individuals, all but one were seed propagated and 72% of survivors were protected by a plant guard. Short‐term survival and establishment of P. hirsuta translocants was increased by producing plants from seeds, and the use of plant guards with localized mulch. We also identified significantly greater root volume, projected area, and diameter for seedlings than cuttings grown plants. Our study successfully identified several key factors that should be considered for the ongoing management of P. hirsuta and vindicates the importance of small experimental trials when planning threatened plant translocations.